MOLECULAR MECHANISMS OF THE INFECTIOUS FACTORS INFLUENCE ON THE PROCESSES OF REPARATION AND NON-SPECIFIC PROTECTION OF THE GASTRIC MUCOSA IN ADOLESCENTS WITH CHRONIC GASTRODUODENITIS - Beketova, H.V.; Hychka, S.H.; Nekhayenko, M.I.; Horgol, N.I.; Horyacheva, I.P.; Soldatova, O.V.; Alekseyenko, N.V. (World of Medicine and Biology, 2019)
In the article, authors present the results of pathohistological and immunohistochemical study of the gastric mucosa (GМ) biopsy in adolescents with chronic gastroduodenitis (СGD) with helicobacteriosis, chronic candidiasis (CC) of the digestive tract (DT), and their combinations, without association with infectious agents. The peculiarities of the reparation processes in GM of adolescents with CGD are: the activity of the CD68 macrophages marker in the lamina propria (LP) in the place of its diffuse infiltration in case of infiltration; with associated infections – in lymphoid follicles; in CC DT – in superficial epithelium and diffuse infiltrate of LP; in the absence of infection – in single cells of the H.p. The activity of the Ki-67 proliferator marker was detected in surface glands and LP in the place of diffuse infiltration in patients of group I; in group II– in lymphoid follicles and superficial glands; in group III – in the place of diffuse infiltration of the LP, superficial and deep glands, in group IV – in the cells of the superficial epithelium. Molecular mechanisms of the pathogens influence and their co-operation with components of congenital immunity and corresponding cellular reaction of the local immune system in adolescents with CGD against the background of CC of GIT shows the highest expression of TLR2 and TLR4 and prevalence of the epithelium, LP and glands, which can testify excitation of receptors. Relation of TLR4/TLR2 expression degree of more than 1.0 was found in patients with CGD associated with H.p., less than 1.0 – in the presence of CC GIT, showing not only the presence but also the severity of the infection. The obtained results confirm the pathogenic role of the Candida genus fungi in the formation and more severe course of CGD in adolescents both in mono- and associated infections. This should be taken into account in creating a program of differentiated treatment in order to achieve a stable remission of CGD, eradication of infectious agents, adequate reparation and restoration of anti-infectious resistance of the GIT mucosa.
Keywords: adolescents; chronic gastroduodenitis; helicobacteriosis; chronic candidiasis; СD68; Кi-67; TLR2; TLR4